Understanding Social Capital in Management of Community Forest in Indonesia - Oktalina, Silvi Nur; Wiyono; Aneka Prawesti Suka; Achmad Rizal H. Bisjoe; Nurhaedah Muin; Digby Race (HABITAT, 2022)
Community forests are defined as forests that grow on private land and are managed by farmers on a small scale. Most of the community forests in Indonesia are managed by farmers, who mostly use social capital in community forest management. Understanding social capital of farmers in managing community forests is important to empower them. This research was a survey conducted by involving 240 respondents in three districts: Bulukumba (South Sulawesi Province), Gunungkidul (Yogyakarta Special Province), and Pati (Central Java Province). The research showed that majority of the farmers believed that community forests can support their livelihoods. Moreover, the research used trust, norm, and network to measure the social capital employed in the community forest management. The result revealed some trusted stakeholders for intervention in community forest management across the study locations were other farmers, farmer group committees, and farmer groups. Meanwhile, the norms that the farmers used in community forest were tradition and custom. In addition, the farming network was identified to understand behavior of the farmers in forest product marketing. A total of 68% of the farmers sell timber, whereas the others (52%) sell crops. Traders are the most important stakeholder in community forest product marketing. From this identification of social capital, we could develop appropriate strategies for intervention to manage the community forests for sustainable community forest management.